Corrosion of aluminum IC metallization with defective surface passivation layer - Comizzoli, R. B.
Corrosion rates and corrosion current of aluminum line patterns passivated with PSG and silicon nitride were measured. Relationships between corrosion and various parameters including temperature, relative humidity, aluminum deposition method, alloying treatment, passivation layer type and defect density and contaminants are reported. A surface treatment which lowers corrosion currents is also discussed.